Fork-Remodeling Helicase Rad5 Preferentially Reverses Replication Forks with Gaps in the Leading Strand. Issue 4 (28th February 2023) - Ling, Justin A.; Gildenberg, Melissa S.; Honda, Masayoshi; Kondratick, Christine M.; Spies, Maria; Washington, M.Todd
Graphical abstract: Highlights: Rad5 is a fork-reversal helicase required for template switching. We monitored the kinetics of fork reversal using a FRET-based assay. Rad5 preferentially reverses forks with gaps in the leading strand. Rad5 reverses forks in the presence of RPA or RNA primers in the lagging strand. The preferred forks are the ones that can be extended during template switching. Abstract: DNA damage bypass pathways promote the replication of damaged DNA when replication forks stall at sites of DNA damage. Template switching is a DNA damage bypass pathway in which fork-reversal helicases convert stalled replication forks into four-way DNA junctions called chicken foot intermediates, which are subsequently extended by replicative DNA polymerases. In yeast, fork-reversal is carried out by the Rad5 helicase using an unknown mechanism. To better understand the mechanism of Rad5 and its specificity for different fork DNA substrates, we used a FRET-based assay to observe fork reversal in real time. We examined the ability of Rad5 to bind and catalyze the reversal of various fork DNA substrates in the presence of short gaps in the leading or lagging strand as well as in the presence or absence of RPA and RNA primers in the lagging strand. We found that Rad5 preferentially reverses fork DNA substrates with short gaps (10 to 30 nt.) in the leading strand. Thus, Rad5 preferentially reverses fork DNA substrates that form chicken foot intermediates with 5′ overhangs that can be extended by replicative DNA polymerases during the subsequent steps of template switching.